Arbitragem no direito de família - Triveloni, Mariana Fernandes (2023)
This present master’s dissertation aims an analysis about the viability of use arbitration in the field of family law as a way of loosen the search for Courts of Justice. The investigation starts with the presentation of Brazilian system family law, its history evolution, concepts and constitutional principles. Also, it was emphasized the role of the alternative dispute resolution, such as mediation, conciliation and negotiation, which are promoted by the nacional laws, as the Civil Code Procedure and the Law of Mediation. However, the heart of this dissertation, is the study of arbitration, approaching its advantages and disadvantages, characteristics, clauses and the difference between the compromise clause and the arbitration clause. To answer the mean question of the investigation, it was presented alternatives for the use of arbitration in the family law, specially in divorce. For this purpose, it was exploited exemples of jurisprudence, doctrine and law. In the conclusion, the dissertation aimed not only answer to the mean question, but also to present the key aspects related to the subject and offer suggestions to increase the efficiency of arbitration, with the purpose to amplify its use and encourage a collaborative law